Influence of storage regimes on physicochemical traits of broiler pectoralis puperficialis muscle using mustard oil: Storage regimes on physicochemical traits of broiler pectoralis (Bangladesh Journal of Animal Science, 2026)
This study was conducted to evaluate the effectiveness of mustard oil as a natural preservative for improving the quality and shelf life of refrigerated broiler breast meat. Boneless broiler breast muscles were collected from the local market of Bangladesh Agricultural University, Mymensingh, and marinated with mustard oil at two concentrations: 1% (T₁) and 5% (T₂), while untreated meat served as the control (T₀). The samples were stored at 4 ± 1 °C for 12 days and analyzed at 0, 6, and 12 days to determine changes in physicochemical properties, proximate composition, instrumental color, water holding capacity (WHC), pH, and lipid oxidation measured by TBARS values. The results revealed that mustard oil significantly (p< 0.05) influenced several quality parameters of chicken meat during refrigerated storage. The treatment with 5% mustard oil (T₂) exhibited higher color stability (L*, a*, and b* values), improved water holding capacity, and lower TBARS values compared with the control and 1% mustard oil treatment, indicating reduced lipid oxidation and better oxidative stability. Although dry matter and crude protein contents showed no significant differences among treatments, ether extract and ash contents varied significantly with treatment and storage duration. The pH values gradually decreased during storage, with mustard oil-treated samples maintaining more favorable pH stability than the control. Overall, the application of mustard oil, particularly at 5%, effectively improved the physicochemical stability and oxidative status of broiler breast meat during refrigerated storage. The findings suggest that mustard oil can serve as a promising natural preservative to enhance the quality and extend the shelf life of refrigerated poultry meat, offering a practical and economical preservation approach for the meat industry.Bangladesh Journal of Animal Science 55 (1): 1-12, 2026